Characterization and evaluation of an arbitrary primed Polymerase Chain Reaction (PCR) product for the specific detection of Brucella species - Qasem, Jafar A. (Saudi J Biol Sci, 2014)
Laboratory detection of Brucella is based largely on bacterial isolation and phenotypic characterization. These methods are lengthy and labor-intensive and have been associated with a heightened risk of laboratory-acquired infection. Antibody based indirect detection methods also suffer from limitations in proper diagnosis of the organism. To overcome these problems, nucleic acid amplification has been explored for rapid detection and confirmation of the presence of Brucella spp. PCR-based diagnostics is useful for screening large populations of livestock to identify infected individuals and confirms the presence of the pathogen. Random Amplification of Polymorphic DNA (RAPD) was performed and identified a 1.3 kb PCR fragment specifically amplifiable from DNA isolated from Brucella. A BLAST search revealed no significant homology with the reported sequences from species other than the members of Brucella. The isolated fragment seems to be a part of d-alanine–d-alanine ligase gene in Brucella sp. Translational BLAST revealed certain degree of homology of this sequence with orthologs of this gene reported from other microbial species at the deduced amino acid level. The sequence information was used to develop PCR based assays to detect Brucella sp. from various samples. The minimum detection limit of Brucella from blood and milk samples spiked with Brucella DNA was found to be 1 ng/ml and 10 ng/ml, respectively. In conclusion, we demonstrated that the PCR based detection protocol was successfully used for the detection of Brucella from various organs and spiked samples of diseased sheep. Diagnosis of Brucellosis by PCR based method reported in this study is relatively rapid, specific and simple.